Proposed Improvement to Minimize Motion Waste in Production of Head Casing Part at PT. Multi Instrumensi With Lean Manufacturing Approach - Williardy Pratama; Agus Alex Yanuar; Meldi Rendra (Universitas Muhammadiyah Yogyakarta, 2019)
PT. Multi Instrumentasi is a manufacturing company that produces water meters. In producing water meters, one of the parts is the head casing. Head casing part consists of two types namely LF-1 and LF-2. Constraints experienced by companies are the inaccessibility of head casing production targets that can hinder the sale of water meters to consumers. For this reason, a proposal to improve the lean manufacturing approach is proposed to minimize the waste that occurs. The stage of the lean manufacturing approach is to identify the production process that occurs using the Process Activity Mapping and Value Stream Mapping. Furthermore, identifying waste that occurs using fishbone diagrams. After identifying waste, waste motion is found in the process of making the head casing part with manual lathes. Subsequently, proposed improvements were made using the Single Minutes Exchange of Die (SMED) method. After the proposed improvement, the company's profitability can be calculated by comparing the existing production costs after the proposed improvements.